Latin American cities with higher socioeconomic status are greening from a lower baseline: evidence from the SALURBAL project. (19th October 2021) - Ju, Yang; Moran, Mika; Wang, Xize; Avila-Palencia, Ione; Cortinez-O'Ryan, Andrea; Moore, Kari; Slovic, Anne Dorothée; Sarmiento, Olga L; Gouveia, Nelson; Caiaffa, Waleska Teixeira; Aguilar, Guilherme Aparecido Santos; Sales, Denise Marques; et al.
Abstract: The characteristics of urban green space have context-dependent associations with socioeconomic status (SES). Latin American cities provide a unique but understudied context to assess the green space-SES associations. We measured the quantity and quality of green space as greenness from satellite-derived Normalized Difference Vegetation Index, and we modeled the relationship between greenness and SES in 371 major Latin American cities between 2000 and 2010. We found that SES was negatively associated with average greenness at city and sub-city scales, which could be explained by urbanization generally improving SES while reducing the provision of green space. About 82% of the cities and 64% of the sub-cities experienced greening or increases in greenness over time. Although with lower average greenness, cities with higher SES had greater greening; however, it was the opposite for sub-cities. We suggest that greening is more likely to take place in peripheral sub-cities where SES tends to be lower. The findings challenge the belief that places with higher SES have better access to environmental resources and amenities; instead, this relationship is context dependent.